On measuring “small potatoes”: spatio-temporal patterning of agrobiodiversity-as-food presents challenges for dietary recall surveys - Keleman Saxena, Alder; Cadima Fuentes, Ximena; Humphries, Debbie L. (Frontiers in Sustainable Food Systems, 2023)
A growing body of research seeks to measure the nutritional contributions of agrobiodiversity to the diets of small-scale farming households. While such articles frequently base analysis on nutritional surveys, particularly using 24-h dietary recall methods, there is as-yet little critical analysis of the benefits and drawbacks of 24-h recalls for assessing the nutritional contributions of agrobiodiversity, or for evaluating the biodiversity conservation implications of particular dietary patterns. The current article draws from mixed-methods research conducted in Cochabamba, Bolivia, between 2011 and 2015. Methods included both ethnographic research and a two-season, household-level survey of 414 households, distributed across a rural–urban gradient between urban Cochabamba and the rural municipality of Colomi. The survey included a 24-h “culinary recall,” recording specific ingredients used to prepare foods, including variety-level information for key crops in the region. Results demonstrate that native crops play an important role in household diets, accounting for around a third of calories reported at the household level, and as much as 57% of caloric availability in the most remote agricultural communities. However, a fine-grained examination of the data shows that nearly a third of all calories reported are provided by potatoes and their derivatives; no other native, improved, or Andeanized crop accounted for more than 1.53% of reported calories. Using ethnographic data, the paper considers reasons for the lack of representation of other crops in dietary recall methods, including the difficulties of capturing the consumption of crops that are seasonal, or consumed as specialty foods under specific circumstances. Drawing from these observations, the paper argues that assessing the importance of local consumption as a driver of agrobiodiversity conservation requires methods that are better attuned to cultural and seasonally driven consumption practices.